Process and Performance of the Chicken Egg Supply Chain at CV Anugerah Akmas Bone Bolango Regency - Nurul Fadly; Ria Indriani; Irwan Bempah (Cita konsultindo, 2024)
The main problem lies in the composition between the increasing demand for purebred chicken eggs while production capacity is stagnant. This study aims to look at the supply chain process, supply chain mechanisms and the performance of the supply chain for broiler eggs. The research is a case study using supply chain operation reference (SCOR) analysis. The results of the analysis show that the supply chain process starts from planning how much to produce, where to supply DOC, how much costs will be incurred in the cultivation process, where the chicken eggs will be distributed, and returning eggs if there are damaged ones. The performance of the chicken egg supply chain at CV Anugerah Akmas is very good, it just needs monitoring to maintain performance.